Health care providers' perceptions of using misoprostol in the treatment of incomplete abortion in Malawi - Cecilie Annette Wagenheim; Hedda Savosnick; Bertha Magreta Chakhame; Elisabeth Darj; Ursula Kalimembe Kafulafula; Alfred Maluwa; Jon Øyvind Odland; Maria Lisa Odland (BMC, 2022)
Abstract Background In Malawi, abortion is only legal to save a pregnant woman's life. Treatment for complications after unsafe abortions has a massive impact on the already impoverished health care system. Even though manual vacuum aspiration (MVA) and misoprostol are the recommended treatment options for incomplete abortion in the first trimester, surgical management using sharp curettage is still one of the primary treatment methods in Malawi. Misoprostol and MVA are safer and cheaper, whilst sharp curettage has more risk of complications such as perforation and bleeding and requires general anesthesia and a clinician. Currently, efforts are being made to increase the use of misoprostol in the treatment of incomplete abortions in Malawi. To achieve successful implementation of misoprostol, health care providers' perceptions on this matter are crucial. Methods A qualitative approach was used to explore health care providers' perceptions of misoprostol for the treatment of incomplete abortion using semi-structured in-depth interviews. Ten health care providers were interviewed at one urban public hospital. Each interview lasted 45 min on average. Health care providers of different cadres were interviewed in March and April 2021, nine months after taking part in a training intervention on the use of misoprostol. Interviews were recorded, transcribed verbatim and analyzed using 'Systematic Text Condensation'. Results The health care providers reported many advantages with the increased use of misoprostol, such as reduced workload, less hospitalization, fewer infections, and task-shifting. Availability of the drug and benefits for the patients were also highlighted as important. However, some challenges were revealed, such as deciding who was eligible for the drug and treatment failure. For these reasons, some health care providers still choose surgical treatment as their primary method. Conclusion Findings in this study support the recommendation of increased use of misoprostol as a treatment for incomplete abortion in Malawi, as the health care providers interviewed see many advantages with the drug. To scale up its use, proper training and supervision are essential. A sustainable and predictable supply is needed to change clinical practice. Plain English Summary Unsafe abortion is a major contributor to maternal mortality worldwide. Unsafe abortion is the termination of an unintended pregnancy by a person without the required skills or equipment, which might lead to serious complications. In Malawi, post-abortion complications are common, and the maternal mortality ratio is among the highest in the world. Retained products of conception, referred to as an incomplete abortion, are common after spontaneous miscarriages and unsafe induced abortions. There are several ways to treat incomplete abortion, and the drug misoprostol has been successful in the treatment of incomplete abortion in other low-income countries. This study explored perceptions among health care providers using misoprostol to treat incomplete abortions and whether the drug can be fully embraced by Malawian health care professionals. Health personnel at a Malawian hospital were interviewed individually regarding the use of the drug for treating incomplete abortions. This study revealed that health care providers interviewed are satisfied with the increased use of misoprostol. They highlighted several benefits, such as reduced workload and that it enabled task-shifting so that various hospital cadres could now treat patients with incomplete abortions. The health care workers also observed benefits for women treated with the drug compared to other treatments. The challenges mentioned were finding out who was eligible for the drug and drug failure. This study supports scaling up the use of misoprostol in the treatment of incomplete abortions in Malawi; the Ministry of Health and policymakers should support future interventions to increase its use.